The Effect of Giving Herbal Medicine Feed with Different Doses on the Growth and Survival of Striped Catfish (Pangasius sp.) Kept Using a Resirculation System - Safitri, Widya; Mulyadi, Mulyadi; Pamukas, Niken Ayu (Jurnal Akuakultur SEBATIN, 2025)
Catfish (Pangasius sp.) is one of the superior freshwater fish commodities in Indonesia which is in great demand by local and foreign communities because the price is relatively affordable. The high demand for patin fish in the market has resulted in many people switching to cultivating patin fish as a livelihood. In cultivation activities, one aspect related to the growth of catfish is feed. The method used in this study is an experimental method using a Completely Randomized Design (CRD). The purpose of this study was to obtain the best dose of feed supplemented with herbal feed in catfish maintenance using a recirculation system. The placement of each treatment in the experimental unit was carried out randomly. The treatments given were PO: Control, P1: 100 ml / kg feed, P2: 200 ml / kg, P3: 300 ml / kg, P4. 400 ml / kg. The best treatment was obtained in treatment P3 with a dose of 300 mL/kg feed which resulted in absolute weight growth of 2.31±0.01 g, absolute length growth of 1.32±0.01 cm, specific growth rate of 1.5310.01%/day, survival rate of 100%, feed conversion ratio of 1.07±0.01 kg